Identification of Goat Skin and Pig Skin as the Raw Material of Rambak Using PCR-RFLP Method - D. Triasih; Y. Erwanto; N. A. Fitrianto (Jurnal Sain Peternakan Indonesia, 2020)
The aim of this research was to detect the skin which comes from goat and pig using PCR-RFLP method so the raw material used in rambak product was discovered. The comparison of combination between goat and pig skin was 100, 75:25, 91:9, 94:6, 97:3, and 99:1. PCR-RFLP uses the universal primary from from mitochondria cytochrome b gen which results in the length of fragment of 359 bp. The restriction enzyme used in the DNA cut is BamHI enzyme and BseDI enzyme. The result of the research showed that seven samples have been successfully isolated perfectly so the total bands of genomic DNA have been obtained which is clearly seen and amplification with target of cytochrome b gen results in PCR product of goat and pig of 359 bp. The digestion's result using BamHI enzyme gets fragment size on 359 bp in length on goat samples and length of fragment size of 359, 244, and 115 bp on samples which contain pig. The digestion results of using BseDI results in fragment size of 359 bp in length on goat samples and the fragment size of 359, 228, and 131 bp in length on samples which contain pig. The conclusion of the research is PCR-RFLP using BamHI enzyme and BseDI enzyme can be used to detect the types of pig skin, but can't be used to detect the goat skin.